139k views
1 vote
Will give 100pts for this question

Will give 100pts for this question-example-1
User Jon Thoms
by
4.6k points

2 Answers

2 votes

Answer:

-3

Explanation:

Lucky guess?

User Marchelbling
by
5.4k points
5 votes

Answer:

-3

Solution,


\frac{24 {x}^(2) + 25x - 47}{ax - 2} = - 8x - 3 - (53)/(ax - 2) \\ \frac{24 {x}^(2) + 25x - 47 }{ax - 2} = (( - 8x - 3)(ax - 2) - 53)/(ax - 2) \\ 24 {x}^(2) + 25x - 47 = - 8a {x}^(2) + (16 - 3a)x - 47 \\

Equating coefficients from both side:


- 8a = 24 \\ a = ( 24)/( - 8) \\ a = - 3

Hope this helps..

good luck on your assignment..

User Peter Friese
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.